Peculiarities of Formation of Senior Pupils’ Active Environmental Position - SkpyrnykSerhiі (Pedagogical Discourse, 2016)
In the article the author analyzes peculiarities and conditions for formation of active environmental position of senior pupils. Analyzing environmental positions of secondary school senior pupils we came to a conclusion that the school system of ecological education mainly leads to enriching pupils’ knowledge of Ecology. Pupils are just informed about ecological problems while preservation of the environment recedes into the background. As a result, the secondary school education forms a passive environmental position of pupils. In the article we analyze factors that lead to formation of active environmental position of senior pupils. Among them a factor of pupils’ motivation is of great importance. To increase the efficiency of environmental education, radical changes in its organization are required. Its effectiveness depends on applying cooperation between a teacher and a pupil and interactive technologies in educational process. Key words: conditions for the formation of active environmental position of senior pupils.